2014
DOI: 10.1371/journal.pone.0100406
|View full text |Cite
|
Sign up to set email alerts
|

Fluid or Fuel? The Context of Consuming a Beverage Is Important for Satiety

Abstract: Energy-containing beverages have a weak effect on satiety, limited by their fluid characteristics and perhaps because they are not considered ‘food’. This study investigated whether the context of consuming a beverage can influence the satiating power of its nutrients. Eighty participants consumed a lower- (LE, 75 kcal) and higher-energy (HE, 272 kcal) version of a beverage (covertly manipulated within-groups) on two test days, in one of four beverage contexts (between-groups): thin versions of the test-drinks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…This null effect for labelling was interpreted as evidence that sensory markers of satiety are likely to overshadow any labelling effects. McCrickerd et al (2014) examined these ideas further by comparing the effects on satiety of changing expectations, by either providing addition information on the test product (e.g. reduces hunger vs. thirst quenching) or by changing its sensory characteristics (thin vs. thick).…”
Section: The Experience Of Food Consumption and Satietymentioning
confidence: 99%
“…This null effect for labelling was interpreted as evidence that sensory markers of satiety are likely to overshadow any labelling effects. McCrickerd et al (2014) examined these ideas further by comparing the effects on satiety of changing expectations, by either providing addition information on the test product (e.g. reduces hunger vs. thirst quenching) or by changing its sensory characteristics (thin vs. thick).…”
Section: The Experience Of Food Consumption and Satietymentioning
confidence: 99%
“…In addition the physical state (i.e., solid vs. liquid) of food and beverage items is thought to influence satiety with implications for obesity. 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…We found subtle evidence of assimilation of label information. Study 1 found that indulgent impressions were partially assimilated, which increased short-term fullness, supporting evidence that cognitive cues can influence appetite [8,10,36]. Congruency between the healthy label and oral experience in study 2 also led to assimilation.…”
Section: Discussionmentioning
confidence: 61%
“…Several studies have demonstrated that label information can alter sensory and hedonic evaluations, satiation and satiety [8,10,14,16,40]. However, other studies found that labels did not alter the eating experience and that ultimately, foods' actual sensory properties and the post-ingestive experience determined product evaluations and appetite [7,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation